Near-infrared squaraine dye encapsulated micelles for in vivo fluorescence and photoacoustic bimodal imaging - Sreejith, Sivaramapanicker (2015)
Combined near-infrared (NIR) fluorescence and photoacoustic imaging techniques present promising capabilities for noninvasive visualization of biological structures. Development of bimodal noninvasive optical imaging approaches by combining NIR fluorescence and photoacoustic tomography demands suitable NIR-active exogenous contrast agents. If the aggregation and photobleaching are prevented, squaraine dyes are ideal candidates for fluorescence and photoacoustic imaging. Herein, we report rational selection, preparation, and micelle encapsulation of an NIR-absorbing squaraine dye (D1) for in vivo fluorescence and photoacoustic bimodal imaging. D1 was encapsulated inside micelles constructed from a biocompatible nonionic surfactant (Pluoronic F-127) to obtain D1-encapsulated micelles (D1micelle) in aqueous conditions. The micelle encapsulation retains both the photophysical features and chemical stability of D1. D1micelle exhibits high photostability and low cytotoxicity in biological conditions. Unique properties of D1micelle in the NIR window of 800–900 nm enable the development of a squaraine-based exogenous contrast agent for fluorescence and photoacoustic bimodal imaging above 820 nm. In vivo imaging using D1micelle, as demonstrated by fluorescence and photoacoustic tomography experiments in live mice, shows contrast-enhanced deep tissue imaging capability. The usage of D1micelle proven by preclinical experiments in rodents reveals its excellent applicability for NIR fluorescence and photoacoustic bimodal imaging.